Inequality, Poverty, Education : A Political Economy of School Exclusion - Ashurst, Francesca; Venn, Couze; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book challenges the practice of exclusion by uncovering its roots in 19th century social and educational policy targeting poor children. Revealing a hidden history of exclusion, this analysis exposes the connections between the state, the education system and social policy, and opens a space for radical alternatives.
Keywords: Science; Science, general